Downtown Los Angeles 52-Story High-Rise and Free-Field Response to an Oil Refinery Explosion. Issue 3 (August 2016) - Kohler, Monica D.; Massari, Anthony; Heaton, Thomas H.; Kanamori, Hiroo; Hauksson, Egill; Guy, Richard; Clayton, Robert W.; Bunn, Julian; Chandy, K. M.
The ExxonMobil Corp. oil refinery in Torrance, California, experienced an explosion on 18 February 2015, causing ground shaking equivalent to a magnitude 2.0 earthquake. The impulse response for the source was computed from Southern California Seismic Network data for a single force system with a value of 2 × 10 5 kN vertically downward. The refinery explosion produced an air pressure wave that was recorded 22.8 km away in a 52-story high-rise building in downtown Los Angeles by a dense accelerometer array that is a component of the Community Seismic Network. The array recorded anomalous waveforms on each floor displaying coherent arrivals that are consistent with the building's elastic response to a pressure wave caused by the refinery explosion. Using a finite-element model of the building, the force on the building on a floor-by-floor scale was found to range up to 1.42 kN, corresponding to a pressure perturbation of 7.7 Pa.